2003
DOI: 10.1002/mds.10590
|View full text |Cite
|
Sign up to set email alerts
|

REM behavior disorder and excessive daytime somnolence in Machado–Joseph disease (SCA‐3)

Abstract: We reported previously that behavior suggestive of rapid eye movement sleep behavior disorder (RBD) was markedly increased in a small population of SCA-3 patients. We, therefore, asked patients and nonpatient attendees at an SCA-3 annual clinic to complete a questionnaire soliciting RBD-like behavior. Our results support the previous observation that RBD-like behaviors are significantly increased in SCA-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 9 publications
2
35
1
Order By: Relevance
“…3,23,24 The average ESS score in our sample (8.67) was considerably higher than that reported in healthy controls (4.86), 23 and 33% had scores ≥ 10, indicating clinical significance. This is in stark contrast from the 5% to 15% prevalence observed in the general population.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…3,23,24 The average ESS score in our sample (8.67) was considerably higher than that reported in healthy controls (4.86), 23 and 33% had scores ≥ 10, indicating clinical significance. This is in stark contrast from the 5% to 15% prevalence observed in the general population.…”
Section: Discussioncontrasting
confidence: 75%
“…19 EDS may also account for impaired cognitive performance in cerebellar ataxia as it has been shown to negatively impact cognitive domains such as attention, memory, motivation and alertness, thus affecting mood, productivity, and quality of life. [20][21][22][23][24] We have also demonstrated that emotional reactivity is maintained by sleep. 25 This role of sleep in emotional processing may contribute to mood regulation.…”
Section: The Effects Of Sleep Dysfunction On Cognition Affect and Qmentioning
confidence: 73%
“…Likewise, sleep complaints have been considered as an important modifier of health-related quality of life in SCAs 12 . The most frequent reported sleep complaints in SCA3/MJD are RLS 13 , RBD 14 , EDS 14 , sleep apnea 12 , and insomnia 12 . Curiously, not only these sleep disorders might be a frequent nonmotor symptom in SCA3/MJD, but may also precede the onset of cerebellar symptoms 2 .…”
Section: Sleep Disorders In Autossomal Dominant Scasmentioning
confidence: 99%
“…Curiously, not only these sleep disorders might be a frequent nonmotor symptom in SCA3/MJD, but may also precede the onset of cerebellar symptoms 2 . When we consider SCA3/MJD patients, frequency rates of RLS are high, reaching about 55% in several studies 12,14,15 . Regarding the dopaminergic system dysfunction of primary RLS, it is speculated that RLS could reflect basal ganglia impairment in patients with SCAs 5 .…”
Section: Sleep Disorders In Autossomal Dominant Scasmentioning
confidence: 99%
See 1 more Smart Citation